Rutgers SNAP GAP Project: Community-Based Participatory Research on SNAP Enrollment - Jennifer Salt Taylor; Delma Yorimoto; Angela Johnsen; Angelica Pozzoli; Cara Cuite; Sara Elnakib (Urban Food Systems Symposium, 2024)
The Supplemental Nutrition Assistance Program (SNAP) is critical in achieving food security, yet many eligible individuals do not enroll due to stigma and various perceived barriers. Food access barriers can be influenced by cultural and social factors. Understanding these aspects helps in tailoring food security programs and interventions to respect cultural values and practices. This project worked to elevate community voices across the state of New Jersey about their experiences and perspectives of SNAP. The SNAP Gap is the difference between who is eligible for and who is participating in SNAP. The objectives of this exploratory study were to identify the reasons why some New Jersey families who may qualify for SNAP are not enrolled in it and propose solutions to increase SNAP enrollment. Working with 6 school districts across the state, the team conducted 19 focus groups with SNAP-eligible caregivers of school-aged children. Additionally, five Department of Human Services administrators were interviewed to learn their ideas on how to increase SNAP enrollment. Focus group findings highlighted issues with the SNAP application process and lack of awareness of the benefits SNAP offers. Interviews with SNAP administrators confirmed challenges in the application process and communication barriers. Based on concerns raised by study participants, and successful existing strategies, the researchers recommended prioritizing promotion of SNAP in schools, streamlining the application process, prioritizing the use of technology to submit the SNAP application and providing updates to the community on any changes about SNAP requirements. This study confirmed that schools are important locations to engage in SNAP promotion. Researchers continue to work with the New Jersey Office of the Food Security Advocate to share study findings to support systems change.
Keywords: supplemental nutrition assistance program; food access; school-based research; food security